2017
DOI: 10.1080/13696998.2017.1326383
|View full text |Cite
|
Sign up to set email alerts
|

The differential rates in cost-related non-adherence to medical care by gender in the US adult population

Abstract: More research is needed to understand the behavioral aspects of gender difference in CRN. Patient-centered healthcare needs to take gender difference into account when addressing cost-related non-adherence behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 18 publications
0
9
1
Order By: Relevance
“…The literature, however, only partially supports this link. 22 , 24 , 26 Conversely, our findings did not corroborate sociodemographic factors reported elsewhere, for example, younger age, 20 22 female gender, 20 , 21 , 23 , 27 lower educational level, 24 and unemployment. 21 Overall, however, this study confirmed the importance of patient-level variables derived from the Integrative Model of Behavioral Prediction.…”
Section: Methodscontrasting
confidence: 99%
See 1 more Smart Citation
“…The literature, however, only partially supports this link. 22 , 24 , 26 Conversely, our findings did not corroborate sociodemographic factors reported elsewhere, for example, younger age, 20 22 female gender, 20 , 21 , 23 , 27 lower educational level, 24 and unemployment. 21 Overall, however, this study confirmed the importance of patient-level variables derived from the Integrative Model of Behavioral Prediction.…”
Section: Methodscontrasting
confidence: 99%
“…Understanding CRMNA and identifying at-risk patients require a clearer knowledge of its determinants and/or correlates. Findings in chronically ill and transplant populations show that sociodemographic risk factors include younger age, 20 22 female gender, 20 , 22 , 23 not being married, 24 a lower education level, 24 unemployment, 21 and being black or Hispanic. 22 , 24 26 Patient-level factors linked with CRMNA include patient-perceived medication regimen-related financial burden, 27 perceived financial stress, 28 financial insecurity regarding healthcare, 28 food insecurity, 25 , 28 health beliefs, 22 , 29 and private health insurance coverage.…”
mentioning
confidence: 99%
“…Of note, although the surveys asked for reports of sex, because such reports encompass a cultural indicator of a person's personal social and cultural identity rather than the biological characteristics of males and females, we use gender instead of sex in the context of CRN behaviors; such behaviors are beyond the biological difference owing to differential cultural roles by men and women. There has been robust discussion in the literature [31][32][33][34] regarding sex differences in the use of health care resources across the life span and the role of gender in contributing to such differences when socioeconomic contexts are incorporated in medical care. Although the literature on gender difference in CRN has increased, 34 to our knowledge, no study has specifically focused on the association of gender with persistence of CRN.…”
Section: Jama Network Open | Health Policymentioning
confidence: 99%
“…Medical costs are influenced by several factors including gender (Owens, 2008;Zhang, Crowe, & Meltzer, 2017). Sex differences between women and men include differences in sex hormones and their effects on system organs (Gambineri & Pelusi, 2019).…”
Section: Gendermentioning
confidence: 99%